Hubungan Pola Makan Berlemak Dan Aktivitas Fisik Dengan Kejadian Hyperkolesterolemia Pada Akseptor KB DMPA Di PMB Ana Amalia - Amalia, Ana; Bachri, Syaiful; Karnasih, I Gusti Ayu (Jember Maternal and Child Health Journal, 2024)
Background: Hypercholesterolemia is a problem that many people complain about, especially DMPA birth control acceptors (Depo Medroxy Progesterone Acetate). The aim of this research is to analyze the relationship between fatty eating patterns and physical activity with the incidence of hypercholesterolemia in Ana Amalia’s PMB. Methods: This research uses a type of Observational research with a cross sectional design. The population was 63 people with a sample size of 54 people and used the chi square test. Results: Ha was accepted, which means there is a relationship between fatty eating patterns and physical activity and the incidence of hypercholesterolemia in Ana Amalia’s PMB. Conclusion: There is a close relationship between fatty eating patterns and physical activity and the incidence of hypercholesterolemia. The more frequently DMPA contraceptive acceptors consume fatty foods, the greater the incidence of hypercholesterolemia, as well as physical activity, people who do light physical activity tend to suffer from hypercholesterolemia, this is because fat in the body is not burned.